Warming-induced radial growth reduction in Betula albosinensis, eastern Qilian Mountains, China - Xiaoya Yan (Elsevier, 2021)
To improve our understanding of how climate change is impacting forest ecosystems in the semi-arid regions of northwestern China, we developed a ring-width chronology for Betula albosinensis growing in the eastern Qilian mountains. We assessed recent radial growth trends and the response of radial growth to climatic factors. The ring width chronology and the basal area increment (BAI) indicate that radial growth of Betula albosinensis has decreased since 1986 CE. Our results show that radial growth is negatively correlated with winter temperature, but that correlations between tree growth and monthly scPDSI from previous June to current September are not significant. Thus, the radial growth of Betula albosinensis from the eastern Qilian Mountains is mainly limited by winter temperature, not by moisture. Winter temperature may affect growth in several ways; for example, higher winter temperatures can increase metabolic stress and lead to earlier bud break, thereby increasing the risk of spring frost damage. In the context of future climate warming, our findings indicate that it is essential to assess growth responses of different tree species growing in arid and semi-arid areas to better predict changes in forest dynamics and carbon cycling.